Development of Anxiety Instructional Guide Apps (AIGA) for Healthcare Workers in Maternal and Child Health (MCH) Clinic - Muslimah Pase; Niasty Lasmy Zaen; Saddiyah Rangkuti (Indonesian Journal of Global Health Research, 2025)
Anxiety among healthcare workers in maternal and child health (MCH) services remains a significant concern, particularly in low- and middle-income countries (LMICs) where access to mental health interventions is limited. This study aimed to develop and evaluate the Anxiety Instructional Guide Apps (AIGA) as a digital solution to reduce anxiety and improve MCH service quality in Medan City, Indonesia. AIGA was developed using the system development life cycle (SDLC) with the waterfall model through stakeholder consultations, UI/UX design, and expert validation. The intervention was tested from May to July 2025 with 10 healthcare professionals (midwives, nurses, and doctors) in two hospitals selected through purposive sampling. Anxiety levels, measured using the Generalized Anxiety Disorder-7 (GAD-7), decreased significantly from a mean of 10.8 ± 1.85 to 5.5 ± 1.08 (mean difference = −5.3 ± 0.48, p < 0.001). User satisfaction was high, with content relevance (M = 4.80 ± 0.42), ease of use (M = 4.70 ± 0.48), and UI/UX design (M = 4.60 ± 0.52) receiving the highest scores. Expert validation gave perfect ratings for content accuracy and accessibility features (5.0 each) and high ratings for technical functionality, user interface, and cultural relevance (4.5 each). These findings indicate that AIGA is a feasible and effective digital intervention to reduce anxiety among healthcare workers in MCH services and has strong potential for integration into LMIC healthcare systems.